Reconsideration of the relevance of mild wedge or short vertebral height deformities across a broad age distribution - Yu, W.; Lin, Q.; Zhou, X.; Shao, H.; Sun, P. (Osteoporosis international, 2014)
Summary Based on an evaluation of vertebral fracture prevalence on lateral radiographs across all age groups in a large cohort, mild or wedge-shaped vertebral body changes identified among adults should be managed as osteoporosis or at least considered as a risk factor for osteoporotic fracture, since they are rare among young subjects. Introduction Radiographic assessment of vertebral fractures is limited by the inability to distinguish mild fractures from congenital mild wedge deformities or vertebrae of short vertebral height. We attempted to quantify the expected background prevalence of these deformities by measuring vertebral fracture prevalence across all age groups in a large hospital-based retrospective Chinese cohort. Methods We reviewed eligible lateral chest radiographs from patients admitted to Peking Union Medical College Hospital during 2011 using the Genant semiquantitative method for vertebral fracture assessment (T4–L2). We evaluated fracture prevalence among subjects by sex, 10-year age group, and fracture severity grades subjectively. We further analyzed characteristics of subjects with mild (grade I) fractures to estimate the relative contribution of congenital mild wedge deformities. Results A total of 10,720 subjects (5,396 men and 5,324 women) with lateral chest radiographs were evaluated. Subjects ranged in age from 0.5 to 97 years with a mean of 51.8 ± 17.4 years (men 52.8 ± 17.6 years; women 50.8 ± 17.2 years). When stratified by 10-year age groups, the prevalence of vertebral fractures was relatively low until about 40 years of age, after which prevalence increased for both genders. Fractures (13 fractures for 9 males and 6 fractures for 5 females) seen in subjects younger than 40 years of age were almost exclusively mild grade fractures. No fractures were identified in subjects younger than 20 years of age. Conclusions Mild or wedge-shaped vertebral body changes on lateral radiographs are rare among young subjects, indicating that when mild vertebral deformities are found among adults, they are likely to be the product of aging and not congenital variation. Clinically, therefore, mild vertebral body changes should be managed as osteoporosis or at least considered as a risk factor for osteoporotic fracture.